Increased acellular and cellular surface mineralization induced by nanogrooves in combination with a calcium-phosphate coating. (February 2016) - Klymov, Alexey; Song, Jiankang; Cai, Xinjie; te Riet, Joost; Leeuwenburgh, Sander; Jansen, John A; Walboomers, X Frank
Graphical abstract: Abstract: The current work evaluated the influence of nanoscale surface-topographies in combination with a calcium phosphate (CaP) coating on acellular and cellular surface mineralization. Four groups of substrates were produced, including smooth, grooved (940 nm pitch, 430 nm groove width, 185 nm depth), smooth coated, and grooved coated. The substrates were characterized by scanning/transmission electron microscopy and atomic force microscopy. Osteoblast-like MC3T3 cells were cultured on the substrates for a period up to 35 days under osteogenic conditions. Differentiation was observed by alkaline phosphatase assay and PCR of collagen I (COLI), osteopontin (OPN), osteocalcin (OC), bone-morphogenic protein 2 (BMP2), and bone sialoprotein (BSP). Mineralization was quantified by a calcium assay and Alizarin Red staining. In addition, acellular mineralization was determined after incubation of substrates in just cell culture medium without cells. Results showed that a reproducible nano-metric (∼50 nm) CaP-layer could be applied on the substrates, without losing the integrity of the topographical features. While no relevant differences were found for cell viability, cells on smooth surfaces proliferated for a longer period than cells on grooved substrates. In addition, differentiation was affected by topographies, as indicated by an increased expression of OC, OPN and ALP activity. Deposition of a CaP coating significantly increased the acellular mineralization of smooth as well grooved substrate-surfaces. However, this mineralizing effect was strongly reduced in the presence of cells. In the cell seeded situation, mineralization was significantly increased by the substrate topography, while only a minor additive effect of the coating was observed. In conclusion, the model presented herein can be exploited for experimental evaluation of cell–surface interaction processes and optimization of bone-anchoring capability of implants. The model showed that substrates modified with CaP-coated coated nanogrooves display enhanced in vitro mineralization as compared to unmodified controls or substrates modified with either nanogrooves or CaP coatings. However, our results also indicated that acellular mineralization assays are not necessarily predictive for biological performance. Statement of significance: The manuscript describes the possibility to combine the mechanical properties of nanosized topographies with the biochemical properties of a calcium phosphate based coating for improvement of surface mineralization. Interestingly, our results demonstrate that further incubation of our surfaces in SBF type media allowed all surfaces to mineralize rapidly to a high extent. Moreover we prove that nanotexture be used to can stimulate and organize mineralization and that the combination surface of a CaP coating and a nanotexture has the potential to be effective as a bone-implant surface. Such experiments will be of considerable interest to those in the research community and industry, who are focusing on bio-mineralization processes and optimization of modern bone-implants.